Solidarity in the Discourse of Protests for Women’s Right Liberation: A Sociolinguistics Study of Mahsa Amini’s Case - Harmia, Citra Dewi (English Department FBS UNP, 2023)
Language as human communication tool plays a substantial as the tool exertion, redemption, and rights fulfillment of the oppressed society. The use of language becomes crucial as a means of discourse on social issues and identity. The protest for women’s rights fulfillment is one of the social issues that gets a lot of attention, both from the demonstration and the discourse used in the movement. Physical abuse led to death which happened to Mahsa Amini in Iran evoked the public's anger which then led to massive protests all around the world. This article aimed to identify the form of solidarity shown in the use of language in the discourse of the liberation of women’s rights specifically in Mahsa Amini’s death case. This research used descriptive-qualitative methodology which used interpretive case study in the protests of Mahsa Amini’s case. The data were in the form of phrases and slogans in English written on the posters used in the protests around the world. The data was collected by searching #MahsaAmini on the search bar of the Instagram application. The data used was only those taken directly from the event of protests. The data then were analyzed by identifying and sorting the speech acts used. Next, the lexical units containing any form of solidarity for the liberation of women’s rights were identified. The result showed that there was a form of solidarity built among the participants of the protests through the identified speech acts.